Penyuluhan Linguistik Forensik: Upaya Pencegahan Kejahatan Berbahasa di Kalangan Pelajar SMK - Herman Didipu; Ishak Y. Majid; Nurul M. Busma; Sri A. Datunugu; Annisa Lamakaraka; Rosalinda Misilu (PT Cendekia Education Center, 2026)
Language politeness and legal awareness in digital communication are critical for high school students to prevent language-based crimes. This community service activity aimed to enhance the understanding of forensic linguistics and mitigate risks such as cyberbullying, hoaxes, and hate speech among students at SMKS Tirtayasa, Gorontalo. The method employed was an educational outreach using a participatory approach, combining case study discussions, lectures, and interactive Q&A sessions. The activity involved six speakers from the service team who presented materials on defamation, threats, religious blasphemy, incitement, and insults, linking them to relevant articles in the Electronic Information and Transactions (ITE) Law and the Criminal Code (KUHP). The results indicated that students gained significant knowledge regarding the legal consequences of improper language use on social media. Observations during the discussion sessions showed increased student engagement and critical awareness, with participants able to identify potential legal violations in daily digital interactions. It is concluded that forensic linguistics outreach effectively improves students' digital literacy and character building. It is recommended that similar programs be expanded to other secondary schools to create a safer digital environment for teenagers.